(untitled) (Orinoquia, 2007)
Titulo en ingles: Use of regional raw materials in the feeding of equine mature creoles in the municipality of Villavicencio. RESUMEN: El presente trabajo fue realizado en Catama, Municipio de Villavicencio. Se utilizaron 9 caballos criollos, adultos, machos, castrados. El ensayo fue dividido en dos fases en las que se evaluaron tres raciones; 1. Ración comercial, como testigo; 2.Ración con 12,4% de pica de arroz y sin aceite crudo de palma africana, ACPA y 3. Ración con 0,86% de ACPA y 20,8% de pica de arroz. Fue empleado un diseño experimental totalmente al azar de tres tratamientos con tres repeticiones. En la primera fase experimental se evalúo ganancia de peso, condición corporal y estado físico. En la segunda fase se determinó la digestibilidad total aparente de las raciones, por el método de colecta total de heces; también se estimó la proteína sérica total pre y postprandial en horas 0, 1, 2, 3 y 4. No se encontraron diferencias significativas (P>0.05) en la ganancia de peso ni en la digestibilidad de las diferentes raciones. Los valores de las proteínas séricas totales fue similar en todos los tratamientos. Se concluye que en equinos adultos de trabajo liviano dietas con 12.4% de pica de arroz y sin ACPA, presentan mejor ganancia de peso y mayor digestibilidad de materia seca y fibra cruda. Palabras clave: Aceite, Arroz, equinos, digestibilidad total. ABSTRACT: The present work was carried out in Catama, which is in the municipality of Villavicencio. Nine adult creoles castrated male horses were used. The feeding trial was divided in two phases during which three different rations were evaluated; 1. a commercially prepared ration was used as a control; 2. a ration with 12.4% of rice fibres by product (pica) without palm oil; 3. a ration with 0,86% of palm oil and 20,8% of rice fibres by product(pica). These rations were used at random in an experimental design of three treatments with three repetitions. In the first experimental phase, the horses were evaluated for weight gain, corporal condition, and physical state. During the second phase, apparent total digestibility was determined by the method of total collection of feces, and also total serum protein was also measured in the three treatments pre and postprandial in hours 0, 1, 2, 3, and 4. No significant differences (P >0.05) where encountered in the weight gains, nor in the digestibility of the different rations. The data of the total serum protein was similar in all the treatments. In conclusion, for equine adults doing light work, the best results were obtained with the ration with 12.4% of rice (pica de) without palm oil resulted in the best weight gain, and greater digestibility of dry matter and raw fiber. Key words: horses, total digestibility, oil, rice.